The role of the director in the Integral Teaching Program - PEI - Nogueira, Maria Ephigênia Cáceres; Fodra, Sandra Maria (Revista Hipótese, 2018)
This article deals with the exploratory research on the role of the director in the management of schools participating in the Integral Education Program of the State Secretariat of Education. In the daily life of the school, the most frequent question to the director when planning a project is: Where is it written that it can? This questioning reveals the understanding that professionals, students and parents and community have of the role of the school. Only what is written in the norms of the education system is done. The Integral Education Program proposes the administrative and legal structure, norms and regulations involving all systems: The Ministry of Education, the Secretariat of Education, the Board of Education and the school in activities related to the objective of supporting organizational and professional development with a view to improving the school's educational activities, a new relationship with the system, Including the principal of the school.
Keywords: Principal; Professional development; Organizational development; Management and leadership